Analisis Strategi Pengembangan Program Pos Pemberdayaan Keluarga (Posdaya) Di Kota Bogor Dan Kabupaten Bogor Analyzing Strategy Development Programs Family Empowerment Post (Posdaya) In The City and County Bogor - Warcito, Warcito (Jurnal Manajemen, 2018)
This study aims (1) analyze the suitability of patterns assistance in implementing programs in Posdaya, (2) analyze the level of satisfaction of the board on the pattern of mentoring programs in Posdaya and (3) analyzing the strategy development programs in the City and County Posdaya Bogor. This research was conducted in Bogor, samples Posdaya 15 Posdaya. This study uses two types of data, primary data and secondary data. Force Field Analysis and Importance Performance Analysis. The results that the board considered that the elements or attributes have good accompaniment (above 80%), except in the frequency attribute mentoring. Analysis on the level of satisfaction of the board to the accompaniment pattern is obtained that the board Posdaya states have satisfied (very good) to Posdaya mentoring program. In general, the results of the analysis of the force field of the four pillars of development Posdaya obtained that the factors driving the value is higher than the value of the inhibiting factors. This indicates that Posdaya be in a position to grow and thrive. Posdaya program development strategies that can be done is to improve and maintain programs that already exist and encourage partnerships with institutions and other institutions.